286 Incidence of pocket haematoma with different anticoagulation strategies in patients undergoing cardiac implantable device implant or revision. (8th December 2021) - Spinoni, Enrico Guido; Santagostino, Matteo; Costantino, Simona; Battistini, Eleonora; Dell'Era, Gabriele; Porcellini, Stefano; De Vecchi, Federica; Mennuni, Marco; Patti, Giuseppe
Abstract: Aims: Direct oral anticoagulants (DOACs) are known for lower bleeding risk than vitamin K antagonist (VKA) in patients with atrial fibrillation (AF). To date, it has not been established whether in such population DOAC may offer reduction of bleeding complication in patients undergoing cardiac implantable electronic device (CIED) implant or revision (substitution, upgrade, or downgrade). We evaluated whether DOACs compared to VKAs, decrease bleeding complications at the time of CIED implant in patients with AF, requiring oral anticoagulant therapy. Methods and results: We present a monocentric observational retrospective study. Patients undergoing implant, generator replacement, or upgrading/downgrading of an intracardiac device (PM, ICD, or CRT) between January 2015 and March 2021 with AF undergoing DOAC or VKA were included. The comparison of risk of clinically significant pocket hematoma at 30-days follow-up in the two-treatment group [DOAC vs. VKA and DOAC vs. VKA without low molecular weight eparin (LMWH) bridge] was performed. Cox proportional hazards regression analysis including main clinical findings was performed to test the primary endpoint. Propensity score matching analysis was performed, with inversed proportional weighted (IPW) propensity score included in the multivariate analysis. 311 patients were included, 146 (46.9%) treated with DOAC and 165 (53.1%) treated with VKA. The incidence pocket haematoma was significantly reduced in patients treated with DOAC compared with VKA (3.4% vs. 13.3%, respectively, P = 0.002), a finding confirmed on multivariate analysis (HR: 3.02, CI: 1.10–8.29, P = 0.032). The incidence of pocket haematoma in patients on DOAC vs. VKA without LMWH bridge therapy was found to be significantly higher in the latter group of patients ( P = 0.033, HR: 2.93, CI: 1.01–8.49, P = 0.48). After adjusting at propensity score with IPW, DOAC use showed decreased risk of pocket haematoma (HR: 0.29, CI: 0.09–0.95, P = 0.42). Conclusions: In patients with atrial fibrillation undergoing CIED implant or revision, DOAC therapy appears to be associated with lower risk of event-related pocket haematoma at 30-day follow-up, even in the absence of bridging with LWMH. Such findings are hypothesis-generating.